NEUROENDOCRINE TUMOURS OF THE APPENDIX IN CHILDREN AND ADOLESCENTS - Neža Salobir; Janez Jazbec; Jože Maučec (Slovenska pediatrija)

(untitled)
Neuroendocrine tumours of the appendix (aNET) are slow-growing, indolent tumours that have an excellent prognosis and rarely show regional nodal metastases. They account for 0.1% of malignant tumours in children. The treatment and follow-up of aNET in children is not standardised. Appendectomy alone is considered curative in most patients, while a more aggressive surgical approach is warranted for incompletely removed tumours or tumours larger than 2 cm. In the last 11.5 years, 23 children and adolescents were diagnosed with aNET in Slovenia.